Improving Purchasing Decisions for MSME's Fashion Products: The Role of E-Personal Branding and Social Media Usage - Bahri, Khoirun Nisa; Rozak , Abdul; Herdiansyah, Yeyep Septian; Widyasari, Raisa Ayu (International Journal of Economics Development Research (IJEDR), 2024)
Indonesia is a country with a very large population with very tempting market potential. The Indonesian fashion industry is in second place as a sub-sector of the creative industry which contributes to increasing the growth of the creative economy in Indonesia. Indonesia's large population is an easy target for business people. The majority of Indonesia's population is Muslim, so it is not surprising that many business people are targeting Muslim communities in Indonesia as their target market. One of the markets with the highest growth in the creative economy sector is the fashion industry, especially Muslim fashion. MSMEs (Micro, Small and Medium Enterprises) are institutions that have the ability to create jobs, distribute income, alleviate people from poverty and play a role in economic growth. In Indonesia, MSMEs have a proportion of more than 90% of the total number of business actors in this country with a workforce of 51.7% to 97.2%. This shows that MSMEs contribute greatly to economic growth in Indonesia. Therefore, further development and research regarding MSMEs in Indonesia is very necessary. Problems that often arise in developing MSME businesses in Indonesia are limited capital and lack of expertise in using digital technology. The use of social media and e-personal branding can be a solution to the problems faced. The aim of this research is to increase purchasing decisions for Muslimah Fashion MSME products through the use of social media and e-personal branding.